Salafism: challenged by radicalization?: violence, politics, and the advent of post-Salafism - Blanc, Théo; Roy, Olivier (Middle East directions, 2021)
In academic and political discourses on radicalization Salafism is routinely identified as the ideological breeding-ground of violent Jihadism and terrorism in both Western and Middle Eastern contexts. It is not clear however, despite an alleged ideological proximity, whether Salafism is a socializing agent of violent Jihadi activists. While the majority of European terrorists were not adherents of strict Salafi orthopraxy before resorting to violence, Salafis themselves publicly denounce terrorism, are very critical of Jihadis, and even often claim to be a barrier against radicalization. Is Salafism therefore a facilitator or a bulwark against violent radicalization? Is there a difference of degree or nature between Salafism and Jihadism? How credible can Salafism be as an instrument for the prevention of radicalization and for de-radicalization? The interrogation of these questions is even more important as it occurs in a contemporary context where Salafism is facing a structural crisis: accusations of breeding terrorism, the phenomenon of “Salafi burn-outs”, the challenge of young generations (“how to be born from a born again?”), the disappearance of traditional Salafi shaykhs, the end of the Saudi sponsorship of transnational Salafism, the autonomization of Salafism vis-à-vis Saudi-Wahhabi tutelage, and unprecedented adaptations to the upheavals of Arab countries’ political systems, all participate to the restructuring of Salafism as an ideology as well as a social force. This raises a number of questions: To what extent is Salafism in crisis? How has violent radicalization challenged Salafism? What are the new venues of activism and modes of engagement through which Salafis ‘reinvent’ Salafism? Are we now entering a post-Salafi era? Ultimately, is the crisis of Salafism good or bad news for violent radicalization? This e-book endeavours to provide the first systematic analysis of these issues based on the expertise of 13 scholars covering case-studies in North Africa, the Sahel/Central Africa, the Middle East, Europe, and South-East Asia.